Aceh Tengah: Penerapan Syariat Islam dan Problematika Kerukunan Umat Beragama - Siregar, Ahmad Sholihin; Qodir, Ibnu (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
The research studied the problems of inter-religious freedom for minority non-Muslims in Shariah implemented region, Central Aceh. This research purposed: 1) identify the inter-religious problems faced by non-Muslims in relation to shariah implementation. 2) describe its background. 3) describe non-Muslim's adaptation to living with the problems. 4) describe government's guarantee of inter-religious freedom for a minority in Central Aceh. This research is held in Central Aceh, is a qualitative field research. To obtain its data, the research used interview, observation and document study. The research found that: 1) there are two major problems an inter-religious affair forth minority. However, those disruptions are coming forth no relation to shariah legislation in Central Aceh. 2) Those little problems found in Central Aceh, 3) the minority adapt to the problems based on the awareness of minorities to their social position, the minorities' attention to Muslims, acceptable rather than bad manner, 4) there is no specific guarantee from government of Central Aceh on religious freedom.